Avaliação qualitativa das decisões do conselho de administração: o caso de uma instituição financeira - Ferreira, Mário Domingues (2005)
This report aims to develop a broad theoretical vision of the conceptual approaches regarding corporate governance, balanced scorecard, decision system and sustainability of one the country´s largest financial corporations. The main goal is the investigation of the administration board´s decisions, evaluating the criteria used in the decision process of this board, checking their coherence with the strategy defined in the management model, technical policies and the corporate governance best practices recommended by the literature and regulatory entities. The methodology used characterizes this work as an applied research, with a qualitative problem approach, based on a case study. Based on ordinary and extraordinary reports of assemblies held between the year 2003 and 2004, the research analyzes the decisions taken by the studied entity´s administration board according to the corporate governance best practices and the management model adopted by this company the Balanced Scorecard. The research results point to conclusive considerations about the question (problem) proposed, indicating (a) the existence of a clear, formal and well defined structure of corporate governance in the company; (b) a relevant contribution of BSC´s concepts, supporting the company´s Board decisions process; (c) the characterization of the decision system´s conceptual structure adopted by the company; (d) the strong adherence between the company´s administration board decisions and the concepts of sustainability. Finally, the work also suggest further studies, due to limitations on the current investigation process.